2016
DOI: 10.11591/ijphs.v5i1.4763
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Analysis of Biomedical Wastes from Selected Health Facilities in Parts of Edo South and its Public Health Implication

Abstract: This study, aimed at the microbial analysis of biomedical waste (BMW) was carried out using 100 samples of 10 different BMW collected in duplicates from 5 busy primary healthcare centers (PHCs).The research findings showed a high prevalence of <em>E.coli</em> (39%) and <em>S.aureus</em> (32%) which were both statistically significant at P≤0.05, while the least isolated organisms were <em>K. pnuemoniae</em> (10%) and <em>B.</em><em> subtilis</em> (4%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…A previous study conducted on samples of biomedical waste from five primary healthcare centres in Edo South, Nigeria, indicated a high prevalence of Escherichia coli (39%) and Staphylococcus aureus (32%) and a lower prevalence of Klebsiella pneumonia (10%) and Bacillus subtilis (4%) [8]. Another study conducted in India reported similar species but with a lower prevalence: Escherichia coli (15%), Bacillis subtilis (12%), Staphylococcus aureus (9%) and Klebsiella pneumonia (6%).…”
Section: Introductionmentioning
confidence: 94%
“…A previous study conducted on samples of biomedical waste from five primary healthcare centres in Edo South, Nigeria, indicated a high prevalence of Escherichia coli (39%) and Staphylococcus aureus (32%) and a lower prevalence of Klebsiella pneumonia (10%) and Bacillus subtilis (4%) [8]. Another study conducted in India reported similar species but with a lower prevalence: Escherichia coli (15%), Bacillis subtilis (12%), Staphylococcus aureus (9%) and Klebsiella pneumonia (6%).…”
Section: Introductionmentioning
confidence: 94%